Suspensions of mixed oxide nanoparticles

By adding acid to the aqueous liquid medium and mechanically treating it, a mixed oxide suspension based on cerium and zirconium with high specific surface area and suitable viscosity was prepared, which solved the problems of increased back pressure and insufficient heat resistance in cGPF, and improved the filtration efficiency and pollutant conversion ability.

CN114502275BActive Publication Date: 2025-04-04RHODIA OPERATIONS SAS
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202080069367.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-01
Filing Date
2020-09-28
Publication Date
2025-04-04
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

The prior art is difficult to prepare mixed oxide suspensions based on cerium and zirconium with high specific surface area and suitable viscosity, and in the preparation of catalytic gasoline particulate filters (cGPF), and there are problems of increased back pressure and insufficient heat resistance.

Method used

By adding acid to the aqueous liquid medium, mixed oxide suspensions of zirconium, cerium, lanthanum and rare earth elements were prepared, and their pH value was controlled between 2.0 and 7.0, ensuring that the size distribution of mixed oxide particles was between 20.0 nm and 900 nm, and the particle size was reduced by mechanical treatment.

Benefits of technology

The high specific surface area and suitable viscosity of the suspension are achieved, the filtration efficiency and heat resistance of cGPF are improved, the back pressure is reduced, and the conversion ability to pollutants is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005169771230000211
    Figure GDA0005169771230000211
Patent Text Reader

Abstract

The invention relates to a suspension of nanoparticles based on a mixed oxide of cerium and zirconium and to the use of said suspension for the preparation of a catalytic gasoline particulate filter.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to European patent application EP 19315119.8 filed on October 1, 2019, the contents of which are fully incorporated by reference into this application for all purposes. In the event of any inconsistency between this application and the EP application that affects the clarity of terminology or expression, reference should be made only to this application.

[0002] The invention relates to a suspension of nanoparticles based on a mixed oxide of cerium and zirconium and to the use of said suspension for the preparation of a catalytic gasoline particulate filter (cGPF). [Technical field]

[0003] Particulate filters are suitable for gasoline engines, in particular gasoline direct injection technology (GDI), where current regulations in Europe and China require compliance with particle number (PN) limits. It would be advantageous to combine the catalytic activity of gaseous pollutant conversion with the reduction of particulates in one step. This can be achieved with catalytic gasoline particulate filters (cGPF). Thus, cGPFs have been developed and offer an effective way to reduce particle and pollutant numbers under all driving conditions. cGPFs are also an effective means of optimizing the aftertreatment layout, reducing the number of catalytic components in the exhaust line.

[0004] The working principle of the cGPF is comparable to that of the established catalytic diesel particulate filter (cDPF). Particles are removed from the exhaust gas by physical filtration using a honeycomb structure similar to the exhaust catalyst substrate (but the channels are blocked at alternate ends). The exhaust gas is thus forced to flow through the porous walls between the channels and the particles are deposited on and in the walls. The catalytic coating provides three-way catalytic (TWC) activity and simultaneously burns carbon monoxide (CO), unburned hydrocarbons (HC) and nitrogen oxides (NO x ) conversion. The TWC coating also supports soot combustion in the cGPF. Filter substrates for gasoline engines are typically made of cordierite, but other substrate compositions such as silicon carbide or aluminum titanate are also possible without any limitation of the present invention. Compared to cDPF, the particle size distribution in gasoline exhaust is different (shifting towards smaller particles), so filters with narrower porosity are required. It is well known that coating of narrow porosity filters is more challenging because back pressure must be minimized to limit the negative impact on engine efficiency, fuel consumption and CO2 emissions. The exhaust temperature of gasoline engines is generally higher than that of diesel engines - therefore the average operating temperature of cGPF is typically higher. This higher temperature also makes the filter easier to regenerate compared to diesel engines. Due to the presence of the TWC carrier coating, part of the soot can be burned continuously. cDPF regeneration is triggered periodically to completely burn the soot.

[0005] The preparation of cGPF generally comprises the following steps: contacting a porous filter substrate with a dispersion of a catalytic composition; drawing the catalytic composition into the channels of the filter substrate by applying a vacuum; drying and calcining the coated filter substrate. The dispersion is typically prepared by mixing a solution of a noble metal (preferably platinum, palladium and / or rhodium) with a mixed oxide based on cerium and zirconium, alumina and other inorganic and / or organic ingredients.

[0006] Mixed oxides based on cerium and zirconium are usually commercialized in solid form. However, the preparation of catalyst dispersions requires an additional step of dispersing the mixed oxide in a liquid. Therefore, a suspension of the mixed oxide in a liquid medium is needed, which can be used directly to prepare the catalyst dispersion. The suspension of the mixed oxide must show a compromise of properties so that it can be easily used and processed during the preparation of the catalytic dispersion. In particular, the suspension must show a viscosity suitable for the preparation of the catalytic dispersion and for the preparation of cGPF. For ease of use and to increase productivity, the proportion of solids in the suspension should also be high enough.

[0007] The characteristics of the mixed oxide also have an impact on the performance of the cGPF. For example, in order to reduce the increase in back pressure caused by the presence of a washcoat on the filter, the washcoat must be located as uniformly as possible within the filter. The particles of the mixed oxide should also easily impregnate the filter while maintaining high heat resistance.

[0008] The suspensions of the present invention aim to achieve this compromise. [Background Technology]

[0009] WO 2017 / 056067 discloses cGPF prepared with a catalytic dispersion having a d50 of about 5 μm.

[0010] US 8,173,087 discloses catalytic dispersions, but it does not disclose the suspension of the present invention.

[0011] US 10,207,253 B1 discloses a catalytic composition comprising particles of CeO 2 and ZrO 2 , which particles may be in the form of individual nanoparticles. No mixed oxides based on cerium and zirconium are disclosed.

[0012] WO 2006 / 030120 discloses mixed oxides for coating filters. It does not disclose the claimed suspension.

[0013] US 7,713,908 discloses suspensions of metal oxide powders having a diameter of no more than 50 nm. For a combination of mixed oxides based on cerium and zirconium with aluminium oxide, the pH of the suspension may be between 5 and 9.

[0014] WO 2017 / 187086 discloses mixed oxides based on cerium and zirconium. WO 2017 / 187086 states that the mixed oxide can be ground to a D50 between 500 nm and 50,000 nm, but does not mention a suspension, nor any acid. For weathering tests of rhodium using a suspension, the D50 was between 1,000 nm and 20,000 nm, thus outside the claimed range. WO 2017 / 187086 therefore does not disclose the claimed suspension.

[0015] Unless otherwise mentioned, the calcinations, more particularly the calcinations after which the values ​​for the specific surface area or the porosity are given, are calcinations in air. For the sake of continuity of the present description, it is also specified that, unless otherwise indicated, the limits are included in the range of values ​​given. This also applies to expressions including "at least" or "at most". [Summary of the invention]

[0016] The present invention relates to a suspension of particles as disclosed in the present disclosure. The suspension comprises particles of at least one mixed oxide of zirconium, cerium, optionally lanthanum and optionally at least one rare earth element (labeled RE) other than cerium and lanthanum in an aqueous liquid medium, the aqueous liquid medium comprising an acid, the acid being an inorganic acid or a carboxylic acid containing from 2 to 12 carbon atoms, preferably from 2 to 8 carbon atoms, the suspension having the following characteristics:

[0017] the pH of the suspension is between 2.0 and 7.0, the latter value being excluded, more particularly between 3.0 and 6.0;

[0018] - the proportion of mixed oxides is between 20.0 wt % and 50.0 wt %, more particularly between 25.0 wt % and 50.0 wt %, even more particularly between 30.0 wt % and 45.0 wt % or between 35.0 wt % and 45.0 wt %;

[0019] - If the mixed oxide contains neither La nor RE, the specific surface area of ​​the suspension is higher than 15 m 2 / g, and if the mixed oxide contains La and / or RE, the specific surface area of ​​the suspension is higher than 21 m 2 / g, the specific surface area is determined after the solid separated from the suspension is calcined in air at 1100° C. for 4 h;

[0020] in:

[0021] the particles of the mixed oxide exhibit a D50 between 20.0 nm and 900 nm, more particularly between 20.0 nm and 800.0 nm, more particularly between 20.0 nm and 500.0 nm, even more particularly between 20.0 nm and 400.0 nm, even more particularly between 20.0 nm and 300.0 nm or between 20.0 nm and 200.0 nm or between 20.0 nm and 100.0 nm;

[0022] The proportions of the elements Ce, Zr, La and RE, expressed by weight of oxide relative to the mixed oxide, are as follows:

[0023] ■ between 20.0 wt% and 55.0 wt% cerium;

[0024] ■ Up to 10.0 wt% lanthanum;

[0025] ■ up to 15.0 wt% of one or more rare earth elements (RE) other than cerium and other than lanthanum;

[0026] ■The remainder is zirconium.

[0027] The present invention also relates to a suspension consisting of:

[0028] ■ particles of at least one mixed oxide of zirconium, cerium, optionally lanthanum and optionally at least one rare earth element (RE) other than cerium and other than lanthanum;

[0029] ■Aqueous liquid medium;

[0030] ■ an acid which is an inorganic acid or a carboxylic acid containing from 2 to 12 carbon atoms, preferably from 2 to 8 carbon atoms;

[0031] The suspension has the following characteristics:

[0032] the pH of the suspension is between 2.0 and 7.0, the latter value being excluded, more particularly between 3.0 and 6.0;

[0033] - the proportion of mixed oxides is between 20.0 wt % and 50.0 wt %, more particularly between 25.0 wt % and 50.0 wt %, even more particularly between 30.0 wt % and 45.0 wt % or between 35.0 wt % and 45.0 wt %;

[0034] - If the mixed oxide contains neither La nor RE, the specific surface area of ​​the suspension is higher than 15 m 2 / g, and if the mixed oxide contains La and / or RE, the specific surface area of ​​the suspension is higher than 21 m 2 / g, the specific surface area is determined after the solid separated from the suspension is calcined in air at 1100° C. for 4 h;

[0035] in:

[0036] the particles of the mixed oxide exhibit a D50 between 20.0 nm and 900 nm, more particularly between 20.0 nm and 800.0 nm, more particularly between 20.0 nm and 500.0 nm, even more particularly between 20.0 nm and 400.0 nm, even more particularly between 20.0 nm and 300.0 nm or between 20.0 nm and 200.0 nm or between 20.0 nm and 100.0 nm;

[0037] The proportions of the elements Ce, Zr, La and RE, expressed by weight of oxide relative to the mixed oxide, are as follows:

[0038] ■ between 20.0 wt% and 55.0 wt% cerium;

[0039] ■ Up to 10.0 wt% lanthanum;

[0040] ■ up to 15.0 wt% of one or more rare earth elements (RE) other than cerium and other than lanthanum;

[0041] ■The remainder is zirconium.

[0042] The invention also relates to a method for preparing a suspension according to the present disclosure. According to this method, a dispersion comprising a mixed oxide M dispersed in an aqueous liquid medium comprising an acid is subjected to a mechanical treatment in order to reduce the size of the particles of the mixed oxide.

[0043] The present invention also relates to the use of a suspension as described in the present disclosure for the preparation of a cGPF and a method for the preparation of a catalytic composition as described in the present disclosure, wherein the suspension is contacted with at least one mineral material and optionally at least one PGM.

[0044] More specific details about these inventions are given below. [Specific implementation method]

[0045] The term "suspension" means a liquid medium in which solid particles are dispersed.

[0046] The suspension comprises at least one mixed oxide of zirconium, cerium, optionally lanthanum and optionally at least one rare earth element (RE) other than cerium and lanthanum in an aqueous liquid medium. The proportion of the mixed oxide in the suspension is between 20.0 wt% and 50.0 wt%, more particularly between 25.0 wt% and 50.0 wt%, even more particularly between 30.0 wt% and 45.0 wt% or between 35.0 wt% and 45 wt%. The proportion in % is represented by the weight of the mixed oxide relative to the total weight of the suspension. For example, a proportion of 40.0 wt% of the mixed oxide corresponds to 40.0 g of the mixed oxide / 100.0 g of the suspension.

[0047] Firstly, the mixed oxide according to the invention is characterized by the nature and proportions of its components. The mixed oxide is based on the elements Ce, Zr, optionally La and optionally at least one RE. For example, the mixed oxide can be based on the elements Ce and Zr; based on the elements Ce, Zr and La or based on the elements Ce, Zr, La and RE.

[0048] The proportion of cerium in the mixed oxide can vary within a wide range. In practice, the proportion of cerium is between 20.0 wt% and 55.0 wt%. The proportion can be between 30.0 wt% and 55.0 wt%, more particularly between 30.0 wt% and 45.0 wt%. The proportion can be between 25.0 wt% and 35.0 wt%.

[0049] The proportion of lanthanum in the mixed oxide is up to 10.0 wt %. The proportion may be between 0 and 10.0 wt %, more particularly between 1.0 and 10.0 wt %.

[0050] The mixed oxide may also contain at least one rare earth element (RE) other than cerium and lanthanum. RE denotes a rare earth element that is neither cerium nor lanthanum. RE may be selected from the group consisting of dysprosium (Dy), erbium (Er), europium (Eu), gadolinium (Gd), holmium (Ho), lutetium (Lu), neodymium (Nd), praseodymium (Pr), promethium (Pm), samarium (Sm), scandium (Sc), terbium (Tb), thulium (Tm), ytterbium (Yb) and yttrium (Y). RE may more particularly be selected from the group consisting of Nd, Y and Pr. The mixed oxide may contain one or two rare earth elements other than cerium and lanthanum. The total proportion of one or more rare earth elements other than cerium and lanthanum is up to 15.0 wt%, more particularly up to 10.0 wt%.

[0051] The mixed oxide may also contain the element hafnium. In fact, this element is usually present in the ores in the natural state in combination with zirconium. The relative proportion of hafnium with respect to zirconium depends on the ore from which the zirconium is extracted. In some ores, the relative proportion of Zr / Hf by weight may be about 50 / 1. Thus, baddeleyite contains approximately 98% ZrO2 and 2% HfO2. The proportion of hafnium is lower than or equal to 2.5 wt%, or even lower than or equal to 2.0 wt%.

[0052] The above-mentioned elements are usually present in the mixed oxide as oxides. However, they may also be present partly in the form of hydroxides or oxyhydroxides. Thus, the elements Ce and Zr, and La or RE (if present), and Hf (if present) are present in the mixed oxide as oxides, but they may also be present in the mixed oxide as oxides and also partly in the form of hydroxides or oxyhydroxides.

[0053] As in the field of mixed oxides, the proportions of the elements are given by weight of the oxide relative to the mixed oxide as a whole. For the calculation of these proportions, the following oxides were considered: CeO2, ZrO2, HfO2, La2O3, RE2O3 (except Pr (for which Pr6O3 was considered) 11 )). Thus, as an example, a proportion of 20.0 wt% of cerium means a proportion of 20.0 wt% of CeO2 in the mixed oxide. The proportions of the elements are determined by common analytical methods like X-ray fluorescence or by inductively coupled plasma mass spectrometry.

[0054] The mixed oxide of the present invention comprises the above-mentioned elements in the above-mentioned proportions, but it may also contain other elements, such as impurities in addition. The impurities may originate from the raw materials or starting materials used in the process for preparing the mixed oxide. The total proportion of impurities may generally be less than or equal to 0.25 wt% (≤ 0.25 wt%), more particularly less than or equal to 0.20 wt% (≤ 0.20 wt%) relative to the mixed oxide.

[0055] Zirconium oxide is the remainder of the composition. The proportion by weight of zirconium is the remainder to 100% of the other elements (Ce, La, RE (if present), Hf (if present)) as mixed oxides. The proportion of zirconium in the mixed oxide is typically higher than 35.0 wt%, more particularly higher than 45.0 wt%, even more particularly higher than 50.0 wt%. The proportion of zirconium is typically lower than 79.0 wt%.

[0056] According to an embodiment, the mixed oxide exhibits a weight ratio ZrO 2 / CeO 2 higher than 1.0, typically higher than 1.5.

[0057] The aqueous liquid medium contains an acid which is an inorganic acid or a carboxylic acid containing from 2 to 12 carbon atoms, preferably from 2 to 8 carbon atoms. The inorganic acid is, for example, nitric acid. Depending on the acid used, the proportion of the acid is between 0.01 wt% and 10.0 wt%, more particularly between 0.5 wt% and 6.0 wt%, expressed by the weight of the acid relative to the entire suspension.

[0058] According to an embodiment, the suspension does not contain any metal oxide other than the mixed oxide disclosed above. A metal oxide is defined as an oxide of at least one metal. The metal may more particularly be selected from the group consisting of Al, Zr or Ti. The metal oxide may be, for example, aluminum oxide, zirconium oxide or titanium dioxide.

[0059] The suspension is also characterized by a high specific surface area. If the mixed oxide contains neither La nor RE, the specific surface area (BET) of the suspension is above 15 m 2 / g, the specific surface area being determined after calcining the solid separated from the suspension in air at 1100° C. for 4 hours. This is the case for mixed oxides of cerium and zirconium. If the mixed oxide contains La and / or RE, the specific surface area (BET) of the suspension is above 21 m 2 / g, the specific surface area is determined after calcining the solid separated from the suspension in air at 1100° C. for 4 hours. This is the case, for example, for mixed oxides of cerium, zirconium and lanthanum or for mixed oxides of cerium, zirconium, lanthanum and at least one rare earth other than cerium and other than lanthanum. In both cases, the specific surface area is generally lower and equal to 40 m 2 / g, more particularly lower and equal to 35m 2 / g, even more particularly lower and equal to 30m 2 / g.

[0060] After calcination at 1000°C for 4 hours in air, the suspension can also exhibit at least 35 m 2 / g, more particularly at least 40m 2 The specific surface area (BET) of 1.5 m / g is determined after calcining the solid separated from the suspension in air at 1000°C for 4 hours. This specific surface is usually lower and equal to 70 m 2 / g, more particularly lower and equal to 65m 2 / g, even more particularly lower and equal to 60m 2 / g.

[0061] According to a specific embodiment, the specific surface area of ​​the suspension disclosed above at 1100° C. and 1000° C. is determined on a solid separated by the following method, which comprises the following steps:

[0062] (i) separating solids from suspensions;

[0063] (ii) then, drying the solid in air at 500° C. for 1 hour;

[0064] (iii) The dried solid was calcined in air at 1100°C for 4 hours or at 1000°C for 4 hours, respectively.

[0065] Therefore, the suspension was subjected to the following steps to determine the specific surface area at 1100°C / 4h or 1000°C / 4h, respectively: (i) → (ii) → (iii) → measurement of specific surface area (BET).

[0066] For the sake of clarity, the expression "specific surface area (BET) of the suspension" therefore refers to the specific surface area (BET) of the solid (mixed oxide) separated from the suspension.

[0067] The term "specific surface area (BET)" is understood to mean the BET specific surface area determined by nitrogen adsorption. The specific surface area is well known to the skilled person and is measured according to the Brunauer-Emmett-Teller method. The method theory was originally described in the journal "The Journal of the American Chemical Society [American Chemical Society], 60, 309 (1938)". More detailed information about the theory can also be found in Chapter 4 of "Powder surface area and porosity [powder surface area and porosity]", 2nd edition, ISBN 978-94-015-7955-1. The nitrogen adsorption method is disclosed in the standard ASTM D 3663-03 (reapproved in 2008). In practice, the specific surface area (BET) can be automatically determined with a device Flowsorb II 2300 or a device Tristar 3000 of Micromeritics according to the manufacturer's guidelines (guidelines of the constructor). They can also be determined automatically with a Mountech Macsorb analyzer model I-1220 according to the manufacturer's instructions. Prior to the measurement, the sample is optionally degassed under vacuum by heating at a temperature of up to 300° C. to remove adsorbed volatile substances. More specific conditions can be found in the examples.

[0068] The suspension may also exhibit a specific porosity measured by mercury porosimetry. In fact, the suspension may also exhibit a pore volume (denoted PV) of pores having a diameter below 300 nm determined by mercury porosimetry. 0-300nm ) is greater than 0.15 mL / g, more particularly greater than 0.25 mL / g.0-300nm It can be between 0.15 and 0.80 mL / g.

[0069] The suspension may also exhibit a total pore volume TPV greater than 0.50 mL / g, more particularly greater than 0.60 mL / g. The TPV may be between 0.50 and 2.00 mL / g, more particularly between 0.50 and 1.50 mL / g, even more particularly between 0.50 and 1.30 mL / g.

[0070] According to a specific embodiment, the pore volume disclosed above is determined according to the following steps:

[0071] (i) separating solids;

[0072] (ii) The solid was dried in air at 500°C for 1 hour.

[0073] Therefore, the suspension was subjected to the following steps to determine the porosity: (i) → (ii) → Measurement of porosity.

[0074] Like the specific surface area, the pore volume therefore refers to the pore volume of the solid (mixed oxide) separated from the suspension.

[0075] The method disclosed above for measuring specific surface area and pore volume comprises step (i), wherein solid is separated from suspension. Step (i) is conveniently performed by filtration. In step (ii), the solid separated from step (i) is dried in air at 500° C. for 1 hour. Step (ii) helps to remove the remainder of the aqueous liquid medium containing acid. After drying step (ii), the solid can form crumbs, which can be conveniently depolymerized. Depolymerization is conveniently performed using a mortar.

[0076] Mercury porosimetry is a standard technique used in the field of porous catalysts and involves gradually pressing mercury into the pores of the porous structure under a controlled pressure. The porosity is measured by mercury intrusion according to well-known techniques in the field. The porosity can be determined using a Micromeritics V 9620 automatic mercury intrusion instrument according to the manufacturer's guidelines. Porosimeters include powder penetrometers. The method is based on the determination of the pore volume as a function of the pore size (V=f(d), V represents the pore volume and d represents the pore diameter). From these data, curve (C) can be obtained, resulting in the derivative dV / dlogD. From curve (C), the pore volume PV measured after calcination at 500°C for 1 hour in air is determined. 0-300nm and total pore volume TPV. The procedure given in the examples is preferably followed.

[0077] The mixed oxide is in the form of particles exhibiting a D50 between 20.0 nm and 900 nm. The D50 may be more particularly between 20.0 nm and 800.0 nm, more particularly between 20.0 nm and 500.0 nm, even more particularly between 20.0 nm and 400.0 nm, even more particularly between 20.0 nm and 300.0 nm, or between 20.0 nm and 200.0 nm, or between 20.0 nm and 100.0 nm.

[0078] The particles preferably exhibit a D90 below 1000 nm. The D90 may more particularly be between 50 nm and 1000 nm, more particularly between 50 nm and 700 nm, even more particularly between 50 nm and 500.0 nm. The D90 is preferably below 200 nm or even below 100 nm.

[0079] According to an embodiment, the suspension exhibits a D50 between 20 nm and 100 nm and a D90 between 50 nm and 120 nm.

[0080] According to another embodiment, the suspension exhibits a D50 between 40 nm and 100 nm and a D90 between 50 nm and 120 nm.

[0081] D50 and D90 are determined from the distribution of the sizes of the particles (by volume) obtained using a laser diffraction particle size analyzer. D50 and D90 have the usual meanings used in the field of particle size analysis. See, e.g. https: / / www.horiba.com / fileadmin / uploads / Scientific / Documents / PSA / PSA_Guidebook.pdf The D50 (median) is defined as the size value corresponding to 50% of the cumulative distribution. Similarly, the D90 is defined as the size value corresponding to 90% of the cumulative distribution.

[0082] D50 and D90 can be determined using a Beckman Coulter LS13320 laser diffraction particle size analyzer (Beckman Coulter, Inc) using standard procedures predefined by the instrument software. Fraunhofer mode ( https: / / www.beckmancoulter.com / wsrportal / techdocs? docname=B05577AB.pdf ). A relative refractive index of 1.6 is used. The method disclosed in the examples can be conveniently used.

[0083] The suspension also contains an acid which is an inorganic acid or a carboxylic acid containing from 2 to 12 carbon atoms, preferably from 2 to 8 carbon atoms. The inorganic acid may more particularly be nitric acid. The carboxylic acid may also contain at least one functional group other than COOH. The functional group may be selected from the group consisting of OH, C=O, anhydride and ester groups. The carboxylic acid may be a monocarboxylic acid, a dicarboxylic acid or a tricarboxylic acid or an alpha-hydroxy-carboxylic acid. The carboxylic acid may more particularly have the formula: R1 -COOH, where R 1 is a straight or branched alkyl group containing from 1 to 11 carbon atoms, more particularly from 1 to 7 carbon atoms. More particularly, the carboxylic acid may be selected from the group consisting of acetic acid, propionic acid, butyric acid, caproic acid, oxalic acid, malonic acid, succinic acid, glutamic acid, adipic acid, maleic acid and citric acid. The carboxylic acid is typically acetic acid.

[0084] The aqueous liquid medium contains water. According to an embodiment, water is the main component of the liquid medium. The aqueous liquid medium can be, for example, water.

[0085] According to another embodiment, the aqueous liquid medium can comprise at least one other liquid miscible with water.Other liquids can be, for example, organic liquids, such as alcohol, ester or ketone.The property and amount of other liquids should preferably make it not affect the stability of suspension.The weight ratio of water / one or more other liquids is preferably between 100 / 0 and 80 / 20, more preferably between 100 / 0 and 90 / 10, even more preferably between 100 / 0 and 95 / 5.

[0086] The aqueous liquid medium also contains an acid. The aqueous liquid medium may also contain impurities present in the mechanically treated mixed oxide. Impurities may be released during the mechanical treatment.

[0087] The pH of the suspension is between 2.0 and 7.0, the latter value being excluded (2.0≤pH<7.0). The pH of the suspension may in particular be between 3.0 and 6.0. It has been observed that the pH has an influence on the ability to reduce the claimed D50 and D90 values ​​and also on the viscosity of the suspension.

[0088] The suspension typically exhibits a viscosity V of less than 1000 cP, more particularly less than 500 cP, even more particularly less than 100 cP. V is measured at 20° C. with a rheometer in cylindrical Couette geometry. The sample is first subjected to a ramp time from 1 s to 1 s over 5 minutes. -1 Increase to 100s -1 The shear rate was then subjected to a shear rate from 100 s -1 Reduced to 1s -1 The viscosity value (V) maintained is the value of the viscosity (V) maintained during the period of shear rate reduction within 10s. -1 The value measured at a shear rate of .

[0089] As regards the use of the suspension according to the invention, this belongs to the field of motor vehicle pollution control catalysis.The suspension according to the invention can be used for the preparation of cGPF.

[0090] The cGPF is typically formed by a porous substrate and a coating comprising a mixed oxide applied to at least a portion of the porous substrate. The coating may be made of one or more layers, at least one layer being made of a catalytic composition comprising a mixed oxide. The coating is made of a catalytic composition similar to that used in TWC technology.

[0091] The preparation of cGPF generally comprises the following steps: (i) contacting a porous filter substrate with an aqueous dispersion of a catalytic composition; (ii) drawing the catalytic composition into the channels of the filter and / or the porous substrate, preferably by applying a vacuum; and (iii) drying and calcining the coated filter.

[0092] About porous substrates

[0093] The porous substrate is typically made of a ceramic material such as, for example, cordierite, silicon carbide, silicon nitride, zirconium oxide, mullite, spodumene, alumina-silicon dioxide-magnesia, zirconium silicate and / or aluminum titanate, typically cordierite or silicon carbide. The porous substrate appears very similar to substrates typically used in emissions treatment systems for gasoline engines. For example, the porous substrate may exhibit a conventional honeycomb structure.

[0094] The filter may take the form of a "flow-through filter" or a "wall-flow filter" (WFF). The filter is preferably a wall-flow filter. A wall-flow filter works by forcing the exhaust gas flow (including particulate matter) through a wall formed of a porous material.

[0095] Wall flow filters typically have a first face and a second face defining a longitudinal direction therebetween.In use, one of the first face and the second face will be the inlet face of the exhaust gas, and the other face will be the outlet face of the treated exhaust gas.

[0096] The wall-flow filter typically has a first and a second plurality of channels extending in a longitudinal direction. The first plurality of channels opens at a first face and closes at a second face. The second plurality of channels opens at a second face and closes at a first face. The channels are preferably parallel to each other to provide a constant wall thickness between the channels. As a result, a gas entering one of the plurality of channels cannot leave the monolith without diffusing through the channel wall into the other plurality of channels. The channels are closed by introducing a sealant material into the open end of the channel. Preferably, the number of channels in the first plurality of channels is equal to the number of channels in the second plurality of channels, and each plurality of channels is evenly distributed throughout the monolith. The channels may have a cross-section of a rectangular, square, circular, elliptical, triangular, hexagonal or other polygonal shape.

[0097] The substrate is typically made of cordierite and exhibits a minimum porosity compatible with the preparation of an efficient cGPF with low backpressure.

[0098] About the catalytic composition

[0099] A coating (usually referred to as a "washcoat") is applied to at least a portion of the substrate. The coating is formed from a catalytic composition prepared from the suspension of the invention. Typically, the catalytic composition is prepared by contacting the suspension of the invention with at least one mineral material and optionally at least one PGM. Thus, the catalytic composition typically comprises:

[0100] (i) mixed oxides (as defined above);

[0101] (ii) at least one mineral material; and

[0102] (ii) optionally at least one PGM.

[0103] The mineral material may be selected from the group consisting of: optionally doped alumina, titania, cerium oxide, zirconium oxide, silicon dioxide, spinel, zeolite, silicate, crystalline silicoaluminophosphate and crystalline aluminum phosphate. The composition may also contain other additives specific to each formulator: H2S scavengers, organic or inorganic modifiers with coating-promoting effects, colloidal alumina, etc. The coating also contains at least one dispersed platinum group metal (PGM), more particularly selected from the group consisting of Pt, Rh or Pd. The PGM is generally in the form of a salt, for example in the form of a nitrate.

[0104] Therefore, the present invention also relates to a method for preparing a catalytic composition, wherein the suspension of the present invention is contacted with at least one mineral material and optionally at least one PGM. The mineral material can be in the form of a solid or a dispersion in an aqueous liquid medium. Since the proportion of mixed oxides in the suspension is usually already high, the mineral material is preferably in the form of a dispersion in an aqueous liquid medium. In addition, the method for preparing the catalytic composition generally comprises adding a liquid, preferably water, to ensure good mixing of the components of the catalytic composition.

[0105] The PGM can be in the form of a solid or an aqueous solution.

[0106] The role of the coating is to convert certain pollutants in the exhaust gas, especially carbon monoxide, unburned hydrocarbons and nitrogen oxides, into products that are less harmful to the environment through chemical reactions. The chemical reactions involved can be the following chemical reactions:

[0107] 2CO+O2→2CO2

[0108] 2NO+2CO→N2+2CO2

[0109] 4C x H y +(4x+y)O2→4x CO2+2y H2O

[0110] The suspensions according to the invention can also be used for the preparation of catalytic converters.

[0111] Method for preparing suspension

[0112] The suspension of the invention is prepared by a process in which a dispersion comprising the mixed oxide M dispersed in an aqueous liquid medium comprising an acid is subjected to a mechanical treatment in order to reduce the size of the particles of the mixed oxide.

[0113] Preparation of dispersions to be mechanically treated

[0114] The mixed oxide M to be mechanically treated may have the same composition as the mixed oxide of the suspension. It may also have substantially the same composition as the mixed oxide of the suspension. The mixed oxide M should preferably exhibit a D90 below 100 μm, more particularly below 60 μm, even more particularly below 50 μm.

[0115] Due to the reduction of the specific surface caused by the mechanical treatment, the mixed oxide M should exhibit a specific surface area which is typically higher than the claimed values, so that the specific surface of the suspension is within the claimed values. The specific surface area of ​​the mixed oxide M to be mechanically treated should be:

[0116] - if the mixed oxide M contains neither La nor RE, above 17m 2 / g, preferably higher than 20m 2 / g; and

[0117] - if the mixed oxide contains La and / or RE, above 25 m 2 / g, preferably higher than 27m 2 / g,

[0118] The specific surface area is determined after calcining the mixed oxide at 1100° C. for 4 hours in air.

[0119] The mixed oxide M can be prepared according to the teachings of WO 2011 / 138255, WO 2016 / 037059, WO 2017 / 072509, EP1527018 or EP 1621251. A convenient technique disclosed in EP 1527018 comprises the following steps:

[0120] a) preparing a mixture comprising a sol of a compound of cerium, lanthanum and optionally RE and a zirconium compound;

[0121] b) adding a solution of a basic compound to the mixture of step a), thereby obtaining a precipitate;

[0122] c) heating the precipitate in an aqueous medium; and

[0123] d) calcining the precipitate thus obtained in step c).

[0124] More specifically, the recipes of the examples of EP 1527018 can be followed or adapted for preparing mixed oxides M, more specifically mixed oxides comprising La and RE.

[0125] Another convenient technique disclosed in WO 2017185224 includes the following steps:

[0126] a) reacting a basic compound with an aqueous solution containing at least a zirconium chloride salt, a cerium salt and optionally at least one rare earth salt other than a cerium salt and a lanthanum salt to form a precipitate, the aqueous solution containing sulfate anions (SO4 2- );

[0127] b) separating the precipitate from the liquid medium;

[0128] c) heating the precipitate obtained in step b) in an aqueous medium;

[0129] d) adding a lanthanum salt, optionally together with a basic compound;

[0130] e) adding lauric acid;

[0131] f) separating the precipitate from the liquid medium; and

[0132] g) calcining the precipitate.

[0133] More specifically, the recipes disclosed in the examples of WO 2017 / 185224 can be followed or adapted for the preparation of mixed oxides M, more specifically mixed oxides comprising La and / or RE.

[0134] Dispersion is prepared by dispersing the mixed oxide M in an aqueous liquid medium comprising acid. The pH of the dispersion obtained is then optionally regulated by adding acid or alkali. The pH of the dispersion is substantially the same as the pH of the final suspension. Dispersion is prepared usually by adding the mixed oxide M in powder form to an aqueous liquid medium comprising acid under vigorous stirring to obtain a uniform dispersion.

[0135] The dispersion of mixed oxide M undergoes mechanical treatment to reduce the size of particle. Use provides enough energy / shearing to reduce the size of particle and does not significantly affect the device of specific surface area. It is believed that the particle of mixed oxide is in the form of aggregate, and it is decomposed into the smaller aggregate of primary particle or primary particle. Device should also provide good mixing to ensure the uniform processing of dispersion. Device can be high pressure homogenizer, wet jet mill, stirred bead mill, high shear stirrer, ultrasonic homogenizer.

[0136] High pressure homogenizers (HPH) involve forcing the dispersion through a narrow gap (e.g. a nozzle with a diameter of 0.1-0.2 mm) at high pressures of about 1500 to 4000 bar, and then allowing the dispersion to relax to atmospheric pressure through the nozzle. The dispersion is then subjected to very high shear stresses, cavitation, turbulence, causing aggregate disaggregation. Shear is caused by the sudden restriction of flow through a restrictive nozzle.

[0137] The technology of the wet jet mill presents some similarities with that of the HPH. In the wet jet mill, the dispersion is compressed in a chamber, usually at 1500 to 2500 bar, and divided into two streams that pass through two corresponding nozzles with a diameter of 0.1-0.2 mm. The dispersion released from the nozzles at atmospheric pressure then forms two liquid jets. When the two nozzles are in relative positions, the two jets collide with each other at high speed. The collision generates high shear stresses on the particles and causes them to deagglomerate. This technology and the HPH are better adapted to initial particle sizes below 60 μm and dispersion viscosities below 5000 cP.

[0138] The technology of agitated bead mills is based on the attrition of solids with hard beads that are in contact with the solids and move at high speed. The beads are usually made of hard materials such as zirconium oxide. The beads preferably exhibit a diameter of less than 500 μm, more particularly between 50 and 500 μm, and even more particularly between 200 and 500 μm. The smaller the diameter, the more beads that can be added in contact with the solid; this enables more collisions to be obtained between the beads and the particles of the solid. More details about the technology can be found in the examples. A person skilled in the art can use the wet grinding conditions disclosed in the examples to obtain the claimed suspension. The agitated bead mill consists of a grinding container containing beads and a device for moving the beads in the container. The device ensures a strong movement of the beads in the container. Different agitated bead mills available on the market can be used in the method of the present invention. The technology of agitated beads is conveniently used to prepare the suspension disclosed in the examples.

[0139] [Example]

[0140] Specific surface area (BET)

[0141] The surface area was determined by N adsorption at liquid N temperature (77 K) on a Micromeritics TRISTAR 3020 analyzer by the BET flow method (multipoint). The specific surface area was calculated by the well-known Brunauer-Emmett-Teller (BET) method. Prior to the measurement, the samples were pretreated in a vacuum oven at 300° C. for 15 min to remove any residual moisture and adsorbed substances.

[0142] As discussed above, the specific surface area (BET) of the suspension is measured on the solid separated from the dispersion.

[0143] Hg porosimetry

[0144] The pore volume is measured using a Micromeritics Autopore IV 9500 mercury porosimeter following the manufacturer's guidelines. The contact angle (θ) uses a value of 130°, and the surface tension of mercury is fixed at 480 dynes / cm. The sample is evacuated to 50 μmHg. The mercury intrusion curve is collected in the pressure range from 0.98 Psi to 30 Psi in the low-pressure cell and from 30 Psi to 60000 Psi in the high-pressure cell; this enables the analysis of pores in a wide range, typically with diameters from 3 nm to 200 μm.

[0145] Particle size analysis

[0146] A laser particle size analyzer is used. A relative refractive index of 1.6 is used. The suspension (about 10 g) is diluted in an aqueous solution (60 mL) with the same pH as the suspension. After ultrasonicating the diluted suspension (5 min; 45 kHz) in an external ultrasonic bath, the diluted suspension is introduced into the measuring cell. Preferably, the measurement is carried out with PIDS (polarization intensity differential scattering) in the range of 45% - 55% (45% < PIDS < 55%).

[0147] Viscosity of the suspension

[0148] A Malvern Kinexus Pro+ stress-controlled rheometer with a cylindrical Couette geometry is used. The rheology of the suspension is measured at 20 °C. First, the sample is subjected to a shear rate that increases from 1 s -1 to 100 s -1 over a ramp time of 5 minutes, and then is also subjected to a shear rate that decreases from 100 s -1 to 1 s -1 over 5 minutes. The viscosity value (V) to be retained is the value measured at a shear rate of 10 s -1 while decreasing from 100 s -1 to 1 s -1 at a shear rate of 10 s.

[0149] XRD

[0150] X-ray powder diffraction patterns were obtained on an X'pertPro MPD powder diffractometer (PANAlytical Company) equipped with a Cu Kα (1.5406 angstroms) radiation source and a linear detector X Celerator detector. Scattering intensity data from 2θ values ​​of 19-85° were collected by scanning at 0.017° steps and counting time of 28s per step. Crystalline phases were identified by matching with the International Diffraction Data Center Powder Diffraction File (ICDD-PDF). The average crystallite size (D XRD ) were determined from the line step width taking into account the instrumental width with the aid of the Scherrer equation, and the lattice parameters were estimated by the standard cubic index method using the intensity of the most prominent peak (1 1 1).

[0151] For all Examples 1-6 and Comparative Examples 1-2, a mixed oxide M having the following composition (expressed by weight of the oxides, %) was used as starting material: Zr / Ce / La 58.5% / 36.0% / 5.5%, characterized by the following specific surface area: 29 m 2 / g. The mixed oxide was prepared according to the teaching of EP 1527018 B1. The powder of the mixed oxide M used in the example initially exhibited a D50 of 4.1 μm and a D90 of 11.5 μm. The crystallite size as determined by XRD was about 8 nm. It was observed that the crystallite size of the mixed oxide remained essentially unchanged after the mechanical treatment.

[0152] Example 1

[0153] Prepare a solution with 120mL deionized water with 0.1g acetic acid to reach a pH of 3.5. Then, prepare a dispersion of mixed oxides by adding 80g of M powder to this 120mL solution. The pH of the dispersion is 6.2. Further adjust the pH by dropwise adding acetic acid (2.5g acetic acid, 96wt%), until the pH (final weight of the dispersion=202.6g) of 4.0 is obtained. With a magnetic stirrer, the dispersion is homogenized for several hours under high stirring.

[0154] Then, for wet grinding, 116 mL of the homogeneous dispersion (167.8 g dispersion) was placed in the bowl of a laboratory bead mill (500 ml capacity container, bowl diameter 10 cm) containing zirconium oxide beads (605.5 g; average size 350 μm). The dispersion was milled in the bowl with a bead stirrer at 1500 rpm for 20 minutes (this corresponds to a duration of 300 minutes / kg oxide).

[0155] Example 2

[0156] Example 1 was repeated under the same conditions as in Example 1.

[0157] Example 3

[0158] Example 3 was repeated under the conditions of Example 1, except that the proportion of mixed oxide M was lower: 25 wt% instead of 39 wt%. Characteristics of the suspension after milling: D50 = 70 nm and D90 = 250 nm. As can be seen in Table I, a decrease in D50 and D90 was observed with a more diluted suspension. The pH also increased significantly during milling from an initial pH of 4.0 to pH 4.6. For the suspension at 1 s -1 Up to 1000s -1 At any shear rate between 20 and 25 °C, the measured suspension viscosity was low, at 3 cP.

[0159] Example 4

[0160] This example was run with a milling time of 40 min instead of 20 min as in Examples 1 and 2. The dispersion was prepared as in Example 1. The slurry was milled in a bowl with beads stirred at 1500 rpm for 40 minutes. The increase in milling time resulted in a decrease in particle size: D50 = 140 nm and D90 = 590 nm. It must be noted that due to some material loss on the surface of the bowl and on the beads, the proportion of mixed oxides in the recovered suspension was found to be 36.6%.

[0161] Example 5

[0162] This example was conducted with a higher pH of the dispersion than in Example 1. The dispersion was prepared as in Example 1, the proportion of mixed oxides was 36.6% (after grinding), and the pH before milling was 6 instead of pH 4. The slurry was milled at 1500 rpm for 40 minutes in a bowl with a bead stirrer. The higher pH slightly affected D50 and D90 compared to Example 4, which tended to increase: D50 = 250 nm and D90 = 650 nm. The pH during milling also increased significantly from an initial pH of 6.0 to pH 6.6.

[0163] Example 6

[0164] The acid used to prepare the dispersion was nitric acid instead of acetic acid. A dispersion of mixed oxides was prepared by adding 80 g of M powder to a solution of 120 mL of deionized water plus a few drops of nitric acid. The pH of the dispersion was 5.9. The pH was then adjusted by adding additional nitric acid to obtain a final pH of 4.0 (a total of 1.3 g of 69 wt % nitric acid was used). The final weight of the prepared suspension was 201.3 g. The slurry was then milled at 1500 rpm for 40 minutes in a bowl with a bead agitator. Characteristics of the particles after milling: D50 = 180 nm and D90 = 590 nm.

[0165] Example 7

[0166] Example 7 was repeated under the conditions of Example 4, except that the mixed oxide M had a different composition (expressed by the weight of the oxides): Zr / Ce / La / Y 60.0% / 30.0% / 5.0% / 5.0%. The mixed oxide was prepared by following the recipe of the example of EP 1527018B1. The proportion of the mixed oxide in the suspension was 36.9 wt%. The final pH was 4.7. The suspension obtained was fluid as was the suspension of Example 4.

[0167] Example 8

[0168] Example 8 was repeated under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxides): Zr / Ce / La / Y / Nd 45.0% / 40.0% / 2.0% / 8.0% / 5.0%. The mixed oxide was prepared by following the recipe of the example of EP 1527018 B1. The proportion of the mixed oxide in the suspension was 37.8 wt%. The suspension obtained was fluid as the suspension of Example 7.

[0169] Example 9

[0170] Example 9 was repeated under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxides): Zr / Ce / La / Nd 63.0% / 30.0% / 1.75% / 5.25%. The proportion of the mixed oxides in the suspension was 34.1 wt%. The final pH of the suspension was 4.7. The suspension obtained was fluid like the suspension of Example 7.

[0171] Example 10

[0172] Example 10 was repeated under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxides): Zr / Ce / La / Y 50.0% / 40.0% / 5.0% / 5.0%. The proportion of the mixed oxides in the suspension was 23.0 wt%. The suspension obtained was fluid like the suspension of Example 7.

[0173] Example 11

[0174] Example 11 was repeated under the conditions of Example 10, except that the proportion of mixed oxide M in the suspension was 19.0 wt %. The suspension obtained was fluid like the suspension of Example 7.

[0175] Example 12

[0176] Example 12 was repeated under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxides): Zr / Ce / La 59.0% / 35.5% / 5.5%. The proportion of mixed oxides in the suspension was 29.0 wt%. The final pH was 4.2. The pH during milling was also increased from an initial pH of 3.8 to pH 4.2. The suspension obtained was fluid like the suspension of Example 4.

[0177] Comparative Example 1

[0178] The pH of the suspension was different from that in the previous examples. The dispersion was prepared as in Example 1, but the pH was 7.0. It was observed that at this pH, the viscosity of the dispersion at about 39 wt% was much higher than that of the suspension of Example 1, so that the dispersion had to be diluted to 34.4 wt% in order to be milled at 1500 rpm for 30 min. After 30 minutes, the viscosity of the suspension became too high and milling was stopped. It was not possible to reduce the D90 below 1 μm (D90 = 7.15 μm).

[0179] Comparative Example 2

[0180] A 27.8 wt% suspension was prepared as in Example 1, but without any acid. The pH of the suspension was 8.3. Milling was performed at 1500 rpm for 30 minutes in a bowl with a bead beater. After 30 minutes, the viscosity of the suspension became too high and milling was stopped. It was observed that the D90 could not be reduced below 1 μm (D90 = 10.7 μm).

[0181] The characteristics of the suspensions are provided in Table I. D50 and D90 were obtained using a laser particle size analyzer LS 13320 from Beckman Coulter.

[0182]

Claims

1. A suspension of particles of at least one mixed oxide of zirconium, cerium, optionally lanthanum and optionally at least one rare earth element (RE) other than cerium and other than lanthanum in an aqueous liquid medium containing an acid which is an inorganic acid or a carboxylic acid containing from 2 to 12 carbon atoms, the suspension having the following characteristics: - the pH of the suspension is between 2.0 and 7.0, the latter values ​​being excluded; - the proportion of the mixed oxide is between 20.0 wt % and 50.0 wt %; If the mixed oxide contains neither La nor RE, the specific surface area of ​​the suspension is higher than 15 m 2 / g, and if the mixed oxide contains La and / or RE, the specific surface area of ​​the suspension is higher than 21 m 2 / g, the specific surface area being determined after calcining the solid separated from the suspension at 1100° C. for 4 hours in air; in: - the particles of the mixed oxide exhibit a D50 between 20.0 nm and 900 nm; The proportions of the elements Ce, Zr, La and RE, expressed as oxides relative to the weight of the mixed oxide, are as follows: ■ between 20.0 wt% and 55.0 wt% cerium; ■ Up to 10.0 wt% lanthanum; ■ up to 15.0 wt% of one or more rare earth elements (RE) other than cerium and other than lanthanum; ■The remainder is zirconium.

2. A suspension consisting of: ■ particles of at least one mixed oxide of zirconium, cerium, optionally lanthanum and optionally at least one rare earth element (RE) other than cerium and other than lanthanum; ■Aqueous liquid medium; ■ an acid which is an inorganic acid or a carboxylic acid containing from 2 to 12 carbon atoms; The suspension has the following characteristics: - the pH of the suspension is between 2.0 and 7.0, the latter values ​​being excluded; - the proportion of the mixed oxide is between 20.0 wt % and 50.0 wt %; If the mixed oxide contains neither La nor RE, the specific surface area of ​​the suspension is higher than 15 m 2 / g, and if the mixed oxide contains La and / or RE, the specific surface area of ​​the suspension is higher than 21 m 2 / g, the specific surface area being determined after calcining the solid separated from the suspension at 1100° C. for 4 hours in air; in: - the particles of the mixed oxide exhibit a D50 between 20.0 nm and 900 nm; The proportions of the elements Ce, Zr, La and RE, expressed as oxides relative to the weight of the mixed oxide, are as follows: ■ between 20.0 wt% and 55.0 wt% cerium; ■ Up to 10.0 wt% lanthanum; ■ Up to 15.0 wt% of one or more rare earth elements other than cerium and lanthanum; ■The remainder is zirconium.

3. The suspension according to claim 1 or 2, wherein The carboxylic acid contains from 2 to 8 carbon atoms.

4. The suspension according to claim 1 or 2, wherein The mixed oxide contains the element hafnium in a proportion lower than or equal to 2.5% by weight, expressed as oxide relative to the weight of the mixed oxide.

5. The suspension according to claim 1 or 2, wherein The mixed oxide contains the element hafnium in a proportion lower than or equal to 2.0% by weight, expressed as oxide relative to the weight of the mixed oxide.

6. The suspension according to claim 1 or 2, wherein The proportion of cerium in the mixed oxide is: - between 30.0 wt% and 55.0 wt%.

7. The suspension according to claim 1 or 2, wherein The proportion of cerium in the mixed oxide is: - between 30.0 wt% and 45.0 wt%.

8. The suspension according to claim 1 or 2, wherein The proportion of cerium in the mixed oxide is: - between 25.0 wt% and 35.0 wt%.

9. The suspension according to claim 1 or 2, wherein The proportion of lanthanum in the mixed oxide is between 1.0 wt % and 10.0 wt %.

10. The suspension according to claim 1 or 2, wherein The acid is nitric acid or has the formula R 1 -COOH carboxylic acid, where R 1 It is a straight-chain or branched-chain alkyl group containing from 1 to 11 carbon atoms.

11. The suspension according to claim 1 or 2, wherein The acid is nitric acid or has the formula R 1 -COOH carboxylic acid, where R 1 It is a straight-chain or branched alkyl group containing from 1 to 7 carbon atoms.

12. The suspension according to claim 1 or 2, wherein The acid is nitric acid or a carboxylic acid selected from the group consisting of acetic acid, propionic acid, butyric acid, caproic acid, oxalic acid, malonic acid, succinic acid, glutamic acid, adipic acid, maleic acid and citric acid.

13. The suspension according to claim 1 or 2, wherein The acid is a carboxylic acid containing at least one functional group other than COOH, the at least one functional group other than COOH being selected from the group consisting of OH, C═O, anhydride and ester groups.

14. The suspension according to claim 1 or 2, wherein The suspension does not contain any metal oxide other than the mixed oxide, the metal oxide being defined as an oxide of at least one metal.

15. The suspension according to claim 1 or 2, wherein The suspension does not contain any metal oxide other than the mixed oxide, the metal oxide being defined as an oxide of at least one metal selected from Al, Zr or Ti.

16. The suspension according to claim 1 or 2, which exhibits at least 35m 2 The specific surface area (BET) of 1.3447 W / g was determined after calcining the solid separated from the suspension at 1000° C. for 4 hours in air.

17. The suspension according to claim 1 or 2, which exhibits at least 40 m 2 The specific surface area (BET) of 1.3447 W / g was determined after calcining the solid separated from the suspension at 1000° C. for 4 hours in air.

18. The suspension according to claim 1 or 2, wherein The suspension exhibits a total pore volume TPV greater than 0.50 mL / g, the TPV being determined by mercury porosimetry on a solid isolated by the following method comprising the steps of: (i) separating the solid from the suspension; (ii) Then, the solid was dried in air at 500°C for 1 hour.

19. The suspension according to claim 1 or 2, wherein The suspension exhibits a total pore volume TPV greater than 0.60 mL / g, the TPV being determined by mercury porosimetry on a solid isolated by the following method comprising the steps of: (i) separating the solid from the suspension; (ii) Then, the solid was dried in air at 500°C for 1 hour.

20. The suspension according to claim 1 or 2, wherein The suspension exhibits a pore volume (PV) of pores having a diameter below 300 nm, as determined by mercury porosimetry. 0-300nm ) greater than 0.15mL / g, PV 0-300nm Determined by mercury porosimetry on a solid isolated by the following method comprising the steps of: (i) separating the solid from the suspension; (ii) Then, the solid was dried in air at 500°C for 1 hour.

21. The suspension according to claim 1 or 2, wherein The suspension exhibits a pore volume (PV) of pores having a diameter below 300 nm, as determined by mercury porosimetry. 0-300nm ) greater than 0.25 mL / g, PV 0-300nm Determined by mercury porosimetry on a solid isolated by the following method comprising the steps of: (i) separating the solid from the suspension; (ii) Then, the solid was dried in air at 500°C for 1 hour.

22. The suspension according to claim 1 or 2, wherein The suspension exhibits a viscosity V of less than 1000 cP, V measured at 20° C. with a rheometer in cylindrical Couette geometry according to the following method: the sample is first subjected to a ramp time from 1 s to 0.5 s over 5 min. -1 Increase to 100s -1 The shear rate was then subjected to a shear rate of 100 s -1 After 5 minutes, it is reduced to 1s -1 The shear rate is reduced and the viscosity value (V) corresponds to the viscosity in 10s during the period of this shear rate reduction. -1 The value measured at a shear rate of .

23. The suspension according to claim 1 or 2, wherein The suspension exhibits a viscosity V of less than 500 cP, V measured at 20° C. with a rheometer in cylindrical Couette geometry according to the following method: the sample is first subjected to a ramp time from 1 s to -1 Increase to 100s -1 The shear rate was then subjected to a shear rate from 100 s -1 After 5 minutes, it is reduced to 1s -1 The shear rate is reduced and the viscosity value (V) corresponds to the viscosity in 10s during the period of this shear rate reduction. -1 The value measured at a shear rate of .

24. The suspension according to claim 1 or 2, wherein The suspension exhibits a viscosity V of less than 100 cP, V measured at 20° C. with a rheometer in cylindrical Couette geometry according to the following method: the sample is first subjected to a ramp time from 1 s to 0.5 s over 5 min. -1 Increase to 100s -1 The shear rate was then subjected to a shear rate of 100 s -1 After 5 minutes, it is reduced to 1s -1 The shear rate is reduced and the viscosity value (V) corresponds to the viscosity in 10s during the period of this shear rate reduction. -1 The value measured at a shear rate of .

25. The suspension according to claim 1 or 2, having a D50 between 20 nm and 100 nm and a D90 between 50 nm and 120 nm.

26. A method for preparing a suspension according to any one of claims 1 to 25, wherein The dispersion comprising the mixed oxide M dispersed in the aqueous liquid medium comprising the acid is subjected to a mechanical treatment in order to reduce the size of the particles of the mixed oxide.

27. Use of a suspension according to any one of claims 1 to 25 for the preparation of cGPF.

28. A process for preparing a catalytic composition, wherein a suspension according to any one of claims 1 to 25 is contacted with at least one mineral material and optionally at least one PGM.

Citation Information

Patent Citations

  • Composition based on zirconium oxide and oxides of cerium, lanthanum and of another rare earth, a method for preparing same and use thereof as catalyst

    EP1527018A2

  • Composition based on zirconium oxide and oxides of cerium, lanthanum and of another rare earth, a method for preparing same and use thereof as catalyst

    EP1527018B1

  • Zirconia porous body and manufacturing method thereof

    EP1621251A1

  • Vanadium oxide catalyst supported on CeO2—ZrO2 for formaldehyde production via partial oxidation of methanol

    US10207253B1

  • Porous composite metal oxide and method of producing the same

    US7713908B2